2014
DOI: 10.1007/s00404-014-3554-4
|View full text |Cite
|
Sign up to set email alerts
|

Does sildenafil have protective effects against ovarian ischemia-reperfusion injury in rats?

Abstract: The results of the current study showed that the sildenafil treatment can be effective in preventing tissue damage and oxidative stress induced by the ischemia-reperfusion created in rat ovaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Congestion, hemorrhage and edema were reduced similar to our study. Further they have assessed oxidative stress index [total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI)] and showed that these scores were also reduced [21]. But there were no data about the differences of follicle count and AMH levels between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Congestion, hemorrhage and edema were reduced similar to our study. Further they have assessed oxidative stress index [total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI)] and showed that these scores were also reduced [21]. But there were no data about the differences of follicle count and AMH levels between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that detorsion can provoke this injury and alone is insufficient to protect ovarian reserve as the follicle count decreases (Ozler et al [38]), several agents, including antiinflammatories and antioxidant drugs, have been evaluated to determine whether they have a protective effect [36]. Experimental studies were performed on rat ovaries to demonstrate the role of different drugs in the protection of ovarian function [36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Gradual detorsion can also reduce reperfusion injury in a rat model of ovarian torsion [37].…”
Section: Effects Of Reperfusion After Detorsion: Experimental Studiesmentioning
confidence: 99%
“…Sildenafil, a phosphodiesterase 5 enzyme inhibitor, causes nitric oxide release from the endothelium, smooth muscle relaxation with increased cyclic guanosine monophosphate (cGMP) and vasodilatation (Kukreja et al, 2005). Due to this known effect, sildenafil has been mostly investigated in reperfusion injury in ovarian tissue and it has been found to be effective in preventing reperfusion injury after ischemia (Ganla et al, 2019;Incebiyik et al, 2015). In addition, the effect of sildenafil in preventing organ damage due to chemotherapeutics was also investigated.…”
Section: Introductionmentioning
confidence: 99%